Efficient preparation of phytase from genetically modified Pichia pastoris in immobilised fermentation biofilms adsorbed on surface-modified cotton fibres. (December 2021) - Ding, Sai; Zhang, Deli; Sha, Yu; Wang, Fangjuan; Liang, Caice; Chen, Tianpeng; Sun, Wenjun; Zhuang, Wei; Yu, Bin; Liu, Dong; Li, Ming; Ying, Hanjie; et al.
Graphical abstract: Highlights: Cotton fiber modified with succinic anhydride is beneficial to cell adhesion. The deletion of PAS_chr2-1_0773 gene promotes the formation of biofilm. The carrier and cell surface properties determine the immobilization effect. The fermentation performance was improved by optimizing the carrier and strain. Abstract: Compared with the traditional suspension fermentation, immobilised biofilm fermentation has advantages of strong resistance, high yield and continuous fermentation and is conducive to improving the industrial fermentation methods. The formation of a biofilm on correct supports is critical to immobilised fermentation. In this study, Pichia pastoris was used to understand and control the modification of surface properties of supports and cells. Following deletion of gene PAS_chr2-1_0773, in P. pastoris △0773, the cell-surface negative charge density decreased and hydrophobicity improved, which was conducive to adhesion. Therefore, according to the changing trend of cell surface properties, cotton fibre was used with succinic anhydride (SA) to modify the carrier for changing the surface properties for efficient conduction of immobilised fermentation. In the fermentation process, the adhesion between the modified cotton fibre and yeast was better than that between an unmodified cotton fibre and yeast, and the additive amount increased by ∼25 %. The enzyme activity of the △0773-cotton-SA fermentation system reached 302.7 U/mL, which was 39.6 % higher than that of the original fermentation system. Therefore, this study provides a guide for significant improvement of immobilised fermentation of fungi.